Participatory governance in the Europe of cross-border regions. Cooperation–boundaries–civil society - Medeiros, E. (Journal of Borderlands Studies, 2021)
One of the consequences of covidfencing processes (see Medeiros et al. 2021a), resulting from the ongoing COVID-19 global pandemic, has been the elevation of cross-border processes and border areas as policy and academic issues. A theoretical avenue through which to encapsulate these contemporary concerns to deal with the closing of borders is the better understanding of the role of cross-border governance and civic participation in mitigating covidfencing worldwide. It is in this context that Peter Ulrich’s latest book on participatory governance in the Europe of cross-border regions makes a timely and welcome contribution. Indeed, it is difficult to dispute the rising importance of cross-border governance structures in Europe in promoting cross-border cooperation, including Euroregions, Eurocities, European Groupings of Territorial Cooperation (EGTC) among others (see Medeiros 2018), to foster European territorial integration (Medeiros et al. 2021b).